Systemic measures on reduction of greenhouse gas emissions in animal husbandry enterprises. A review - I. V. Petrunina; N. A. Gorbunova (Пищевые системы, 2022)
The paper presents a review of different approaches to solving problems arising upon greenhouse gas emission from activities of animal husbandry enterprises. The sector of ruminant animal production is under close attention for ecological reasons due to its significant contribution to emission of enteric methane (CH4) and an effect on global climate change. Moreover, analysis of the main sources of methane emission in the agricultural sector of the agro-industrial complex, including by species of livestock and poultry, is given. An impact of a feeding system, feeds and feed additives in use and manure storage on nitrogen losses is estimated. In this connection, the authors examine several promising scientific and practical development results that are aimed to reducing emissions and formulating a strategy for controlling direct emissions of greenhouse gases in animal husbandry that do not jeopardize animal productivity, especially in the context of sustainability. Practical activities that envisage the development of the complex of measures for reduction of greenhouse gas emissions are examined. Potential strategies for mitigating their consequences were divided into the following main categories: animal raising, changes in animal diets and manipulations with rumen. Furthermore, several other measures facilitating an increase in livestock productivity and reduction of the negative effect on the environment were taken. Eco-economic methods for assessing emissions of harmful gases in production of animal husbandry products are considered and the necessity of developing simpler cost-effective technologies for quantitative assessment of greenhouse gas emissions and a search for solutions to preserve favorable climate is emphasized. When assessing greenhouse gas emissions, the loss sizes and cumulative ecological damage are taken into account. Realization of strategies for emission reduction should lead to an increase in animal productivity and a decrease in the negative effect of animal husbandry on the environment.